Uji Kandungan dan Tingkat Kesukaan Rasa Puding Laguna pada Baduta Gizi Kurang di Wilayah Kerja Puskesmas Abeli - Nurmi, Wati; Ananda, Siti Hadrayanti; Desa, Desiderius Bela (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2022)
Malnutrition is a problem of nutrition that still widely found in the community, especially in the Abeli Health Center where the case of malnutrition in January-May in 2022 is 33 people. One of the efforts to tackle lack of nutrition is to provide additional food in the form of Laguna pudding which is made from local food, namely purple sweet potatoes and dragon fruit. This study aims to determine the nutritional content and level of flavor of Laguna pudding in toodler Nutrition. This research is a descriptive research with a complete random design. The population of this study was that all of the malnutrition in the Abeli Health Center amounted to 33 people with sampling techniques using total sampling. This research data was obtained by sharing a questionnaire to find out the level of preference while the nutritional content was obtained by conducting carbohydrate, protein and beta -carotene examinations in the MIPA laboratory at Halu Oleo University. Data were analyzed descriptively. The results showed that the highest carbohydrate content in Laguna pudding A1 was 35.52%, while in Laguna pudding A2 it was 29.20%. Likewise, the protein content of Laguna Pudding A1 is more, namely 1.91%, while Laguna Pudding A2 is 1.55%. Then the beta-carotene content in Laguna Pudding A1 is 10.66 g/g while Laguna pudding A2 is 9.95 g/g. Then the level of liking for Laguna pudding A1 mostly liked as many as 23 people (69.7%) the rest did not like as many as 10 people (30.3%). While the Laguna pudding A2 mostly disliked as many as 22 people (66.7%) and liked as many as 11 people (33.3%). The conclusion of this study is the content of Carbohydrates, Protein and Beta-carotene and the level of preference for Pudding Laguna A1 is higher than A2. Suggestions for the health center, especially nutrition workers, are to disseminate the benefits of Laguna Pudding to overcome malnutrition and for parents who have toodler to provide Laguna Pudding as additional food for Toddler.